Sleep Paralysis and Hallucinosis - Gregory Stores (Behavioural Neurology)
Background: Sleep paralysis is one of the many conditions of which visual hallucinations can be a part but has received relatively little attention. It can be associated with other dramatic symptoms of a psychotic nature likely to cause diagnostic uncertainty. Methods and results: These points are illustrated by the case of a young man with a severe bipolar affective disorder who independently developed terrifying visual, auditory and somatic hallucinatory episodes at sleep onset, associated with a sense of evil influence and presence. The episodes were not obviously related to his psychiatric disorder. Past diagnoses included nightmares and night terrors. Review provided no convincing evidence of various other sleep disorders nor physical conditions in which hallucinatory experiences can occur. A diagnosis of predormital isolated sleep paralysis was made and appropriate treatment recommended. Conclusions: Sleep paralysis, common in the general population, can be associated with dramatic auxiliary symptoms suggestive of a psychotic state. Less common forms are either part of the narcolepsy syndrome or (rarely) they are familial in type. Interestingly, sleep paralysis (especially breathing difficulty) features prominently in the folklore of various countries.